In Situ Extracorporeal Shock Wave Lithotripsy (ESWL) and ESWL after Push Back For Upper Ureteric Calculi: A Comparative Study - Regmi, Sunil; Adhikari, Sunil Chandra; Singh, Rabin Raj; Bastakoti, Rabi; Yadav, Saroj (Journal of Nobel Medical College, 2017)
Background: ESWL is one of the most important modality for the treatment of urolithiasis. In situ ESWL is a non-invasive and safe procedure for renal and upper ureteric stones in selected cases & can be performed on outpatient basis. However, some urologists claim a higher success rate of ESWL after push back procedures for upper ureteric calculi.Materials & Methods: This prospective study was done to compare the results of treatment of upper ureteral calculi by in situ ESWL and ESWL after push back. 90 consenting patients with single upper ureteric stones of ≤ 1 cm in size with no distal obstruction were selected and divided into two groups. 50 patients in group 1 were treated by in situ ESWL while 40 patients in group 2 were treated by push back followed by ESWL.Results: Better clearance was achieved with ESWL after push back (92.5% clearance after 90 days) than with in situ ESWL (90% clearance after 90 days) but it was not statistically significant (p>0.05). The mean shock wave was 1994 ± 449 for in situ ESWL group and 1757.5 ± 255 for ESWL after push back group, which was statistically very significant (p